Cost Effectiveness Analysis of Anticoagulants as The Therapy of Corona Virus Disease 19 (Covid-19) - Saputra, Andy Kurniawan; Andayani, Tri Murti; Trisnawati, Ika (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Hypercoagulation is a condition characterized by increased thrombosis and is caused by various factors, one of which is SARS-CoV-2 virus infection. Anticoagulants are the main therapeutic options such as heparin and enoxaparin. The administration of these two drugs can reduce coagulation parameters such as D-dimer, PT, and fibrinogen values. The purpose of this study was to analyze the cost-effectiveness comparison of heparin and enoxaparin as anticoagulants in severe and critical COVID-19 patients. This study is an analytical observational study with a retrospective cohort design from a provider perspective. The research subjects were severe and critical COVID-19 patients who met the inclusion and exclusion criteria at Dr. Sardjito General Hospital in the period January 2021 - January 2022. The effectiveness of anticoagulants was seen through a decrease in the D-dimer value to a value of < 500 ug/ml on day 14 in medical records, safety was assessed from the incidence of bleeding recorded in medical records, while the average direct cost data during the patient's hospitalization was studied to determine cost-effectiveness with the Incremental Cost-Effectiveness Ratio (ICER). The achievement of D-dimer value < 500 μg/ml for the heparin group was 39.5% while the enoxaparin group was 48.4%, the result showed no significant difference (p=0.293). All subjects did not experience bleeding. The average direct medical cost of the heparin group was Rp. 31,296,577 and enoxaparin was Rp. 55,205,810. The ACER calculation of heparin and enoxaparin was Rp. 79,233,841 and Rp. 114,061,591 with an ICER of Rp. 2,686,431 for a decrease in D-dimer value reaching < 500 ug/ml. This shows that enoxaparin is better at reducing D-dimer values despite having a higher cost than heparin.